2010
DOI: 10.1116/1.3511511
|View full text |Cite
|
Sign up to set email alerts
|

Direct transformation of a resist pattern into a graphene field effect transistor through interfacial graphitization of liquid gallium

Abstract: The authors found that an extremely thin resist pattern on a silicon dioxide can be directly transformed into a graphene channel through interfacial graphitization of liquid gallium. These patterned graphene field effect transistors show p-type field effect conductance characteristics and a maximum conductance modulation of 100% against an applied gate voltage range from −50 to +50 V at room temperature, which is almost identical to the on/off ratio of 2. These conductance modulation ratios improved with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports. Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports.…”
Section: B Mechanism Of Ga Evaporation Processcontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports. Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports.…”
Section: B Mechanism Of Ga Evaporation Processcontrasting
confidence: 99%
“…First, carbon has negligible solubility in liquid Ga. 19 In this paper, we report selective graphene growth from diamondlike carbon (DLC) film. 14 This means that Ga can dissolve at least negligible amounts of carbon, which is promising, because copper, the outstanding catalyst of monolayer graphene fabrication, also has a low solubility of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…19,20) We have demonstrated that liquid gallium can catalyze the amorphous carbon at the interfacial region. [21][22][23][24][25][26] Graphene nanoribbons were transformed from amorphous carbon templates of amyloid fibrils by solid-phase graphitization within the gallium vapor ambient. 21) Moreover, a large area of graphene can be formed using methane CVD combined with gallium vapor.…”
mentioning
confidence: 99%